Urban size and KIBS vertical disintegration: Evidence from Lombardy - Roberto Antonietti; Giulio Cainelli (European Regional Science Association (ERSA), 2012)
A recent strand of the economic literature has emphasised the role of services, and in particular knowledge-intensive business services (KIBS), as a primary source of knowledge creation and diffusion. Since this transferring process often occurs through strong face-to-face interactions, the role of spatial proximity becomes crucial. Theoretical and empirical literature show that the geographic concentration of industry induces firms to vertically disintegrate their production, due to the lowering of transport and governance costs as well as to the reduction of opportunism in managing transactions. However, the evidence is primarily based on manufacturing firms, whereas little or no attention is given to service firms. In this paper we try to fill this gap by estimating the effects of urban agglomeration on knowledge intensive business service firmsâ exteuro™ vertical disintegration in a longitudinal context, with reference to the Lombardy region in Italy. Data used in this work are drawn from AIDA, a commercial database collected by Bureau Van Dijck gathering information on balance sheets data as well as the geographical position of Italian joint stock companies. Relying on this rich firm-level dataset, we build a sample of almost 17.000 KIBS firms located in Lombardy over the period 2004-2009, and we estimate both a first difference and an instrumental variable GMM model in which, as dependent variable, we use both the share of purchased business services and the share of material inputs, while, as explanatory variables, we include firm size, age and population size at the municipality and local labour system level. In so doing, we estimate the impact that the short-run variations in urban size have on the short-run variations in the degree of vertical disintegration of KIBS, while controlling for potential endogeneity issues due to unobserved heterogeneity and simultaneity, and for the robustness of our measure of urban size to alternative specifications. Our results complement previous cross-sectional evidence and point to a positive and statistically significant effect of urban size on the degree of vertical disintegration. In addition, we find that this effect is particularly strong for professional KIBS and for the purchase of business services rather than for technological KIBS and for the purchase of material inputs.
Keywords: C33; D22; R12; L24; 330; agglomeration; KIBS; urban size; vertical disintegration